Opportunities and Challenges in Translational Research: The Development of Photodynamic Therapy and Anti-Vascular Endothelial Growth Factor Drugs. Issue 1 (2021) - Marko, Christina Kaiser; Miller, Joan W.
Abstract: The development of photodynamic therapy and anti-vascular endothelial growth factor agents have revolutionized the treatment of retinal diseases, transforming the retina subspecialty by ushering in an age of pharmacological treatments for a wide range of diseases, including age-related macular degeneration (AMD).